Growth and yield of Sunflower (Helianthus annuus)in additive Intercropping system with Mung bean. - Ashna Khalil kaka Ahmed; Sami Muhammad Amin Maaroof (Zanco Journal of Pure and Applied Sciences, 2022)
Some crops perform better in intercropping systems with other crops relative to their solcropping . Sunflower (Helianthus annuus L.) was adopted to be studied in a field experiment within an additive intercropping system with mungbean (Vigna radiata L.) in a three rows in combinations (1:3 and 1:4 and 1:5) sunflower-Mung bean intercropped and sole cropped for studding growth , yield components and yield traits during the summer of 2021 at two different agro ecological locations of the governorate of Erbil- Iraq. Experiments were triplicated in a randomized complete block design (RCBD), Each location was a parcel of a local farmers land in the villages of Shamamr (Latitude: 406227, Longitude: 397954 rainfall isocline (350 mm y-1)) and Dukalla (Latitude: 358033 m, Longitude: 3993384 m),at the last of the semi insured and the first of the non-insured rainfall zones respectively . Shamamr location suppressed Dukalla location in most of morphological traits at the ages of 20 days after sowing (DAS), nd 60 DAS. Treatment row combination (1:3, 1:4 and 1:5) showed advantages in yield component traits over sole cropping of sunflower might be due to resources gains as solar radiation, conditioning heat environment and space .No advantages of intercropping were observed among cropping systems in seed yield while the treatment (1:5) possessed the highest Harvest index (0.6). Sunflower in Shamamr location is believed to perform better under intercropping system. More planting geometry is recommended to obtain more precise results. References : Abràmoff, M.D., Magalhães, P.J. and Ram, S.J., 2004. Image processing with ImageJ. Biophotonics international, 11(7), pp.36-42. Anas, M., Jabbar, A., Sarwar, M.A., Ullah, R., Abuzar, M.K., Ijaz, A. and Latif, S., 2017. Intercropping Sunflower with Mung beanfor improved productivity and net economic return under irrigated conditions. Pakistan Journal of Agricultural Research, 30(4). Bindi, M. and Olesen, J.E., 2011. The responses of agriculture in Europe to climate change. Regional Environmental Change, 11(1), pp.151-158. Dizayyee , Aryan Suad Ahmed . (2019).Modes of Interference Compatibility of Wheat, Chickpea and Wild mustard Intercropping in Different Row Proportions. PhD Dissertation , University of Salahaddin , College of Agricultural Engineering Sciences. Gebru, H., 2015. A review on the comparative advantages of intercropping to mono-cropping system. Journal of Biology, Agriculture and Healthcare, 5(9), pp.1-13. Jeon, D.J., Ki, S.J., Cha, Y., Park, Y. and Kim, J.H., 2018. New methodology of evaluation of best management practices performances for an agricultural watershed according to the climate change scenarios: A hybrid use of deterministic and decision support models. Ecological Engineering, 119, pp.73-83.(abstract). Jubr Al-Layla, M. and Shahadha Khalid Al-Juheishy, W., 2012. EVALUATION OF DIFFERENT INTERCROPPING SYSTEM IN SUNFLOWER (Helianthus annuus L.) ANDMUNGBEAN (Vigna radiata L.). Mesopotamia Journal of Agriculture, 40, pp.62-74. Khan, M. N., Shoaib Muhammad, Mahboob Asrar, M. S. Ashraf, and Qamar Rafi. "MB (Vigna radiata) intercropping enhances productivity of late season irrigated cotton in Punjab." Asian Journal of Agriculture and Biology 8, no. 4 (2020): 472-479. Lithourgidis, A.S., Dordas, C.A., Damalas, C.A. and Vlachostergios, D., 2011. Annual intercrops: an alternative pathway for sustainable agriculture. Australian journal of crop science, 5(4), pp.396-410. Mousavi, S.R. and Eskandari, H., 2011. A general overview on intercropping and its advantages in sustainable agriculture. Journal of Applied Environmental and Biological Sciences, 1(11), pp.482-486. Nawar, A.I., Salama, H.S. and Khalil, H.E., 2020. Additive intercropping of SF and soybean to improve yield and land use efficiency: Effect of thinning interval and nitrogen fertilization. Chilean journal of agricultural research, 80(2), pp.142-152. Shi, H., Tian, H., Lange, S., Yang, J., Pan, S., Fu, B. and Reyer, C.P., 2021. Terrestrial biodiversity threatened by increasing global aridity velocity under high-level warming. Proceedings of the National Academy of Sciences, 118(36). Vandermeer, J.H., 1992. The ecology of intercropping. Cambridge University Press. (book) .